The shielding effect of glycerol against protein ionization in electrospray mass spectrometry - Mendes, M. A.; Chies, J. M.; Dias, ACD; Astofi, S.; Palma, Mario Sergio [UNESP] (Wiley-Blackwell, 2003)
Most commercial recombinant proteins used as molecular biology tools, as well as many academically made preparations, are generally maintained in the presence of high glycerol concentrations after purification to maintain their biological activity. The present study shows that larger proteins containing high concentrations of glycerol are not amenable to analysis using conventional electrospray ionization mass spectrometry (ESI-MS) interfaces. In this investigation the presence of 25% (v/v) glycerol suppressed the signals of Taq DNA polymerase molecules, while 1% (v/v) glycerol suppressed the signal of horse heart myoglobin. The signal suppression was probably caused by the interaction of glycerol molecules with the proteins to create a shielding effect that prevents the ionization of the basic and/or acidic groups in the amino acid side chains. To overcome this difficulty the glycerol concentration was decreased to 5% (v/v) by dialyzing the Taq polymerase solution against water, and the cone voltage in the ESI triple-quadrupole mass spectrometer was set at 80-130 V. This permitted observation of a mass spectrum that contained ions corresponding to protonation of up to 50% of the ionizable basic groups. In the absence of glycerol up to 85% of the basic groups of Taq polymerase became ionized, as observed in the mass spectrum at relatively low cone voltages. An explanation of these and other observations is proposed, based on strong interactions between the protein molecules and glycerol. For purposes of comparison similar experiments were performed on myoglobin, a small protein with 21 basic groups, whose ionization was apparently suppressed in the presence of 1% (v/v) glycerol, since no mass spectrum could be obtained even at high cone voltages. Copyright (C) 2003 John Wiley Sons, Ltd.